Review on characterization of deamidation in therapeutic proteins by mass spectrometric methods - Taraj, Krenaida (Technium BioChemMed, 2025)
Deamidation is a critical post-translational modification that influences the stability, structure, and function of therapeutic proteins, impacting their efficacy in clinical applications. This spontaneous process, primarily affecting asparagine (Asn) and glutamine (Gln) residues, leads to the formation of aspartic acid (Asp) and glutamic acid (Glu), respectively, and is influenced by environmental factors such as pH, temperature, and ionic strength. Understanding deamidation is essential, particularly in monoclonal antibody (mAb)-based therapies, where structural integrity determines therapeutic performance. Mass spectrometry (MS) has emerged as a powerful tool for deamidation analysis due to its sensitivity, accuracy, and ability to characterize complex protein modifications. Various MS approaches, including top-down, middle-down, and bottom-up methods, facilitate the identification and quantification of deamidation events. Additionally, reversed-phase liquid chromatography (RPLC), often integrated with MS, supports therapeutic protein analysis but faces challenges such as peak broadening, secondary interactions, and protein denaturation. Recent advancements in proteomics and MS techniques continue to refine our understanding of deamidation, offering new insights into protein stability, aging-related modifications, and disease mechanisms. This review aims to provide a comprehensive perspective on deamidation studies, emphasizing its implications for biopharmaceuticals and therapeutic protein development.